2014
DOI: 10.1111/jmwh.12244
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nulliparous Women with Spontaneous Labor Onset Admitted to Hospitals in Pre‐active versus Active Labor

Abstract: Introduction-The timing of when a woman is admitted to the hospital for labor care following spontaneous contraction onset may be among the most important decisions that labor attendants make as it can influence care patterns and birth outcomes. The aims of this study were to estimate the percentage of low-risk, nulliparous women at term who are admitted to labor units prior to active labor and to evaluate the effects of the timing of admission (i.e., pre-active versus active labor) on labor interventions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Finally, a study involving nurses, physicians, and new mothers found that all three groups believed nursing care was critical to maternal and newborn outcomes, including caesarean and breastfeeding rates 42 . Other studies have reported that changes in hospital policy, especially regarding labor definitions, are associated with decreased rates of cesarean birth 21,43‐46 . For example, defining active labor as starting at 6 cm, rather than 4 cm, and allowing longer lengths of labor (especially for nulliparous women and women with an epidural) are associated with increased rates of SVB 45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a study involving nurses, physicians, and new mothers found that all three groups believed nursing care was critical to maternal and newborn outcomes, including caesarean and breastfeeding rates 42 . Other studies have reported that changes in hospital policy, especially regarding labor definitions, are associated with decreased rates of cesarean birth 21,43‐46 . For example, defining active labor as starting at 6 cm, rather than 4 cm, and allowing longer lengths of labor (especially for nulliparous women and women with an epidural) are associated with increased rates of SVB 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that changes in hospital policy, especially regarding labor definitions, are associated with decreased rates of cesarean birth 21,43‐46 . For example, defining active labor as starting at 6 cm, rather than 4 cm, and allowing longer lengths of labor (especially for nulliparous women and women with an epidural) are associated with increased rates of SVB 45,46 . Another body of research indicates that midwife‐led care and labor support are associated with increased rates of SVB 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Neal et al [8] studied the outcome of nulliparous women with spontaneous onset of labor in US population. They included 114 women in pre-active labor.…”
Section: Discussionmentioning
confidence: 99%